ACS Photometry of Newly Discovered Globular Clusters in the Outer Halo of M31 - Mackey, A. D; Huxor, A; Ferguson, A. M. N; Tanvir, N. R; Irwin, M; Ibata, R; Bridges, T; Johnson, R. A; Lewis, G (The Astrophysical journal, 2007)
We report the first results from deep ACS imaging of 10 classical globular clusters in the far outer regions (15 kpc R sub(p) 100 kpc) of M31. Eight of the clusters, including two of the most remote M31 globular clusters presently known, are described for the first time. Our F606W, F814W color-magnitude diagrams extend 6 3 mag below the horizontal branch and clearly demonstrate that the majority of these objects are old ( 10 Gyr), metal-poor clusters. Five have [Fe/H] 6 -2.1, while an additional four have -1.9 [Fe/H] -1.5. The remaining object is more metal-rich, with [Fe/H] 6 -0.70. Several clusters exhibit the second-parameter effect. Using aperture photometry, we estimate integrated luminosities and structural parameters for all clusters. Many, including all four clusters with projected radii greater than 45 kpc, are compact and very luminous, with -8.9 M sub(V) -8.3. These four outermost clusters are thus quite unlike their Milky Way counterparts, which are typically diffuse, subluminous (-6.0 M sub(V) -4.7), and more metal-rich (-1.8 [Fe/H] -1.3).